Vitamin D supplementation in Polycystic ovary syndrome - Grzywna, Natalia; Zdun, Sylwia; Walczak, Klaudia; Walczak, Patrycja; Nemeczek, Sylwia; Merkisz, Konrad; Grzybowski, Jakub; Marciniak, Agnieszka; Jaskuła, Karolina; Orłowski, Władysław (Journal of Education, Health and Sport, 2022)
Introduction and Purpose. Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in women of reproductive age worldwide. Patients may present with a wide range of symptoms. According to the most commonly used Rotterdam criteria, the presence of 2 out of 3 criteria is required for diagnosis: clinical and/or biochemical markers of hyperandrogenism (HA); ovulation disorders (oligo- or anovulation); polycystic ovaries on ultrasound (PCOM); and exclusion of disorders mimicking the clinical features of PCOS. The basis of treatment are birth control pills, metformin and antiandrogens. The pathogenesis of the syndrome is not fully understood. The aim of the study is to summarize the potential health benefits of vitamin D supplementation for women with PCOS based on publications from the last 10 years available on Pubmed. State of knowledge. Vitamin D receptors have been identified not only in calcium-regulating tissues, but also in many reproductive organs, such as the ovary (especially granulosa cells), uterus, placenta, testes, as well as hypothalamus and pituitary gland. In recent years, there have been studies analyzing the effect of vitamin D supplementation on the hormonal balance, metabolism and clinical symptoms in women with PCOS. Summary. The results of studies on vitamin D supplementation in women with PCOS are mixed. Some of them are promising and confirm a beneficial effect on glucose metabolism and insulin resistance, lipid metabolism, hormonal balance, alleviation of HA-related symptoms, improvement of menstrual frequency; while the results of other studies do not show significant improvement and do not confirm these effects. Therefore, there is a need for further research on the relationship between the pathogenesis of PCOS and vitamin D and the impact of its supplementation.